Dyeing Behavior and Multi-Functionalities of Polylactide/Poly (Ethylene Terephthalate) Conjugate Fibers Produced by High-Speed Melt-Spinning. Issue 1 (16th September 2020) - Kawahara, Yutaka; Takarada, Wataru; Takeda, Koji; Ikeda, Yoshimitsu; Onda, Kouki; Kikutani, Takeshi
Abstract: Various types of conjugate fibers comprised of polylactide (PLA) and polyethylene terephthalate (PET), with their blend in the sheath, PET as the core, were produced by high-speed melt-spinning. Due to the higher glass transition temperature of PET, the orientation-induced crystallization only occurred in the PET core. The crystalline and continuous PET core of the conjugate fibers effectively suppressed the shrinkage during dyeing, even in a pressurized water bath at 130 °C comparable to the commercial level, to less than 5% while achieving a color strength higher than 15. Post-annealing in the restrained mode could effectively cause the fine PET fibrils embedded in the sheath to rise out from the surface of the fibers during dyeing by the sliding friction force between the fibers. The PET fibrils rising out from the sheath were strong enough and showed an entangling behavior which would be useful to fabricate non-woven fabrics. The amorphous PLA domains exposed on the fiber surface showed the bacteriostatic activity valuable for the inhibition of the formation of biofilms.